An Affecting of Community-Based Tourism Toward Integrated Sustainable Homestay in Malaysia - Wan Abd Aziz, Wan Mohd Amin; Muhammad Abi Sofian, Abd. Halim; Mohd Shaladdin, Muda (2016)
In Malaysia, a Model of Community Based Tourism that has been discussed by a numbers of scholars becomes a significant role to the homestay industry that operated by community in a rural area. In depth, this model took account various resources and stakeholders in order to integrate the sustainability of rural homestay development. However, a number of rural homestay operators are lacking of knowledge toward the crucial of integrated sustainable model as well as practicing in their business. Thus, the objective of this paper is to study the model of community-based tourism as an influencing factor that affecting to the integrated sustainable homestay which are operating in Malaysia rural areas. The results of multiple regressions analysis indicate that the only factors of socio-economy, organizational culture and government are support significantly affecting to the integrated sustainable homestay. Generally, the results indicated that most of homestay operators are not really satisfying the important factors of community-based tourism that affecting to their integrated sustainable homestay. Therefore, the concept and model of Community-based Tourism become crucial applicable in developing an awareness among rural homestay operators toward the integrated of homestay sustainability.